The conditions of formation of self-educational competence of future teachers - Kifik, Natalia (Przegląd Wschodnioeuropejski, 2018)
The article discloses the pedagogical conditions of the formation of selfeducational competence of future teachers at credit system of education. Subject of this article is a characteristic of pedagogical conditions among which formation of internal motives of future teacher, formation of self-educational competence, need for continuous self-educational activity; formation of the identity of the student as active subject of activity; improvement of system of formation of self-educational competence of future teacher have been disclosed. Process of training assumes active cognitive activity of the trainee by means of the use of a complex of tutorials which the multimedia and technological complex, electronic manuals belong to. For identification of pedagogical conditions of formation of self-education of future teachers at credit system of training we defined research strategy which personality and activity based and informational approaches act upon.